1999
DOI: 10.1097/00003246-199905000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Do the components of heat and moisture exchanger filters affect their humidifying efficacy and the incidence of nosocomial pneumonia?

Abstract: Despite differences in their components, the two HMEFs that were tested achieved similar performances in terms of humidification and heating of inspired gases. Only one episode of endotracheal tube occlusion was detected, and very few patients (three in each group) had to be switched to an active heated humidifier. No difference was observed either in the rate of tracheal colonization or of ventilator-associated pneumonia. These data show that the Humid-Vent Filter Light and the Clear ThermAl HMEFs are suited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Absolute inspired gas humidity values obtained with the most efficient hygroscopic and hydrophobic HMEs were 29.1 Ϯ 1.8 mg H 2 O/L (21) and 30.8 Ϯ 1.5 mg H 2 O/L (18), respectively, as measured using the psychrometric method. We are aware of only three reported cases of endotracheal tube occlusion with these HMEs, including one in a patient who experienced massive tracheal bleeding before the occlusion (9,13). This suggests that an absolute humidity of 30 mg H 2 O/L (with the psychrometric method) or even a bit less may be sufficient to prevent most cases of endotracheal tube occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absolute inspired gas humidity values obtained with the most efficient hygroscopic and hydrophobic HMEs were 29.1 Ϯ 1.8 mg H 2 O/L (21) and 30.8 Ϯ 1.5 mg H 2 O/L (18), respectively, as measured using the psychrometric method. We are aware of only three reported cases of endotracheal tube occlusion with these HMEs, including one in a patient who experienced massive tracheal bleeding before the occlusion (9,13). This suggests that an absolute humidity of 30 mg H 2 O/L (with the psychrometric method) or even a bit less may be sufficient to prevent most cases of endotracheal tube occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…HMEs used in this study were poorly performing ones. With newer hygroscopic HMEs, endotracheal tube occlusion seems unusual (8)(9)(10)(11)(12)(13)(14)(15), even with prolonged use (16)(17)(18).…”
mentioning
confidence: 99%
“…9,12,16,26,27 A further limitation of our study is that we did not compare the heated humidifier with a passive conditioning device such as an HME. Despite several limitations, [28][29][30][31] the HME is a simple to use and cost-effective device that is widely employed in general anaesthesia. It would be therefore be of interest to compare mucociliary function and pulmonary complications following use of a heated humidifier or HME.…”
Section: Characteristicmentioning
confidence: 99%
“…(3) Therefore, a viable alternative would be to use heat and moisture exchangers (HMEs) on such equipment.A hydrophobic HME contains an inline, disposable, hygroscopic, bacteriostatic sponge (microbiological filter, Figures 1B and 1D) that reduces device contamination, thus protecting patients from microbial contamination. (4) Lucato et al (5) demonstrated that the dead space volume and resistance caused by the addition of an HME did not change the VC or respiratory muscle strength values in volunteers evaluated during spontaneous breathing. To our knowledge, there have been no studies aimed at determining whether the addition of a microbiological filter has a relevant impact on those variables in patients with impaired pulmonary function.…”
mentioning
confidence: 99%